Prognostic Significance of Percutaneous Coronary Intervention for First Acute Myocardial Infarction with Heart Failure: Five-Year Follow-Up Results - Zichao Cheng; Yuchen Shi; Hongyu Peng; Donghui Zhao; Qian Fan; Jinghua Liu (Cardiology Research and Practice)
Objective. The study aimed to investigate the incidence and influencing factors of heart failure after 5 years of percutaneous coronary intervention (PCI) for first acute myocardial infarction. Methods. A total of 1235 patients, diagnosed as acute myocardial infarction and treated with PCI in Beijing Anzhen Hospital, Capital Medical University, from January 1, 2014, to December 31, 2014, were enrolled. Based on the exclusion criteria, 671 patients were followed up to obtain echocardiographic results 5 years after the onset of myocardial infarction (from January 1, 2019, to December 31, 2019). Of 671 patients, 62 were lost to follow-up. Finally, 609 patients were recruited in this study. According to the results of the echocardiographic examination, patients were divided into a heart failure group (n = 97) (LVEF < 50%) and a nonheart failure group (n = 512) (LVEF ≥ 50%). The clinical characteristics were compared between the two groups, and the influencing factors of heart failure after 5 years of PCI in patients with acute myocardial infarction were analyzed using logistic regression and receiver-operating characteristic (ROC) analyses. Results. Of 609 patients, 97 had heart failure within 5 years after PCI for first myocardial infarction, with an incidence of 15.9%. Multivariate regression analysis finally examined the predictors related to the occurrence of heart failure, including age (aOR, 1.008; 95% confidence interval (CI), 1.054–1.123; P ≤ 0.001), peak troponin I level (aOR, 1.020; 95% CI, 1.006–1.034; P = 0.004), left ventricular ejection fraction (LVEF) (during admission) (aOR, 0.908; 95% CI, 0.862–0.956; P ≤ 0.001), and left ventricular end-diastolic dimension (LVEDD) (at admission) (aOR, 1.136; 95% CI, 1.016–1.271; P = 0.025). Conclusion. In this study, the incidence of heart failure (LVEF < 50%) in patients with acute myocardial infarction who underwent PCI was 15.9% at a five-year follow up. Age, peak troponin I level, and LVEDD (at admission) were risk factors for heart failure, while LVEF (at admission) of patients during hospitalization was a protective factor for heart failure.